A pluriatividade dos agricultores no contexto local do município de Princesa - SC - Hansen, Jairo Jacó (2011)
In the present research, the Pluralactivity in the town of Princesa SC, approaches mainly the aspects of the rural families. It s a case study that involved data collect in a part of the rural dwellers of the town, which has as its main goal is to identify the recent aspects of the agriculture and non-agriculture occupations of the dwellers. The methodology applied is based on concepts present in national bibliographies and focused on social spatial formation category, emphasizing occupation aspects, productive farming specialization as well as population migration and micro region urbanization of São Miguel do Oeste, State of Santa Catarina.